Student Attitudes Toward Digital Badges for Instructional Design Competency-Based Education - Watson, Sunnie Lee; Watson, William R.; Huang, Wanju; Janakiraman, Shamila; Dufault, Katie H. (Social Education Research, 2023)
This case study examines the self-reported attitudes of graduate students in an online instructional design master’s program regarding its use of digital badges to track and record students’ required professional competencies. The study sought to evaluate student attitudes towards the program and its use of badges. All enrolled students, approximately 300, were asked to complete a course improvement survey that included the Attitudinal Learning Inventory which measured their perceptions of how their attitudes changed toward the use of digital badges for competency-based education and what aspect of the course most impacted their attitudes. 211 students responded to the course improvement survey. 14 students, ranging from those who had completed the program to those who had only completed a single semester were also interviewed to gather richer data detailing their positive and negative experiences with demonstrating competence through the digital badge process. Results indicated that the students had positive attitudes regarding the use of digital badges across all components of their attitudes-cognitive, affective, behavioral, and social. Participants noted how the badges helped their learning and motivation while also identifying aspects of the program that worked best for them and areas which could be improved. Implications are that digital badges for tracking competencies can improve learning and motivation, but the implementation benefits from significant planning and process revision.